The Effect Of Job Training, Job Supervision And Employee Commitment To Job Performance - Seno Andri; Mandataris Mandataris (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
This research was conducted at PT. Multiguna Lestari Abadi Kelurahan Selensen Indragiri Hilir. The purpose of this study is to determine the effect of job training, work supervision and employee commitment to the work performance of production employees at PT. Multiguna Lestari Abadi Kelurahan Selensen Indragiri Hilir. Job training, work supervision and employee commitment as independent variables (X) while job performance as dependent variables (Y). The problem in this study is production results that have not reached the company's target for the last 5 years, accompanied by the presence of several employees who are absent or late as seen from company data and supported by expert opinions. The sample of this study was taken as many as 53 respondents with a total of population size. Data obtained from the results of questionnaires distributed using questionnaires using census / total sampling techniques. and then processed to then be tested with statistics through SPSS 22. From the results of the tests conducted show that job training has a positive and significant effect on employee work performance, work supervision has a positive and significant effect on work performance, employee commitment has a positive and significant effect on work performance, then job training, work supervision and the application of employee commitment to work performance, where the calculation (20.840) table (3.18) and significance value (0.000) 0.05.